Degating of AlSi10Cu2Fe High-Pressure Die Casting Component Using Resonance Vibration Technique - Tey, Jing Yuen; Yeo, Wei Hong; King, Yeong Jin; Ramli, Rahizar (Springer, 2020)
The high-pressure die casting process is meant for high volume production rate mainly used in the automotive industry. An efficient method to separate the die-cast components from the main sprue and runner system is crucial to improving the productivity of the manufacturing processes. Conventionally casting components are often separated with the use of a grinding wheel machine, trimming machine or pneumatic hammer. Often these techniques require customized machine design in trimming the cast part as each die casting gate design might be different from one another, especially when there is a change in production cast model. This may incur higher set-up cost and additional configuration time. It is unfavourable in the manufacturing production line that handles small batch high variation of casting model in the small/medium casting industry. Thus, this paper introduced an alternative degating technique with the use of a shaker machine to match the resonance of the casting component natural frequency to separate the die-cast component from the casting tree. The proposed method can overcome the drawback of the conventional method by eliminating the additional configuration time required when there is a change in different casting part design. Die casting parts employed in this study were constructed by AlSi10Cu2Fe aluminium alloy. Experimental modal analysis was performed to verify the natural frequency calculated through finite element analysis. The correlated finite element model was then employed for harmonic response analysis to compute the frequency response of input excitation location against output stress response at the gate. The results from the analysis showed that the first natural frequency mode could induce a bending mode at the gate and created the highest stress concentration at the location. Next, an experiment was carried out by exciting the first natural frequency to the casting part using a shaker machine. In the experiment, the die-cast components were able to break away within 0.31 s at its first natural frequency. This observation was found to be in agreement with the simulation results, whereby the degating time of 0.27 s was obtained. Therefore, the present study has shown that an efficient degating of casting components process can be achieved via introducing a correct mode of vibration excitation. © 2019, American Foundry Society.